The clinical features and short‐term treatment outcomes of scirrhous cord: A retrospective study of 32 cases. (12th July 2020) - Duggan, M.; Mair, T.; Durham, A.; Pengelly, T.; Sherlock, C.
Summary: Scirrhous cord (SC) is an uncommon complication of castration, characterised by chronic infection of the spermatic cord remnant. It is reported that surgical excision of the infected tissue is the most effective means of treatment, but there are few published studies assessing the outcomes of horses treated for SC. The aims of this retrospective study were to describe the clinical features and short‐term outcomes in horses treated for SC at two equine hospitals in the UK. The clinical records of horses diagnosed with SC over a 10‐year period were reviewed. A diagnosis of SC was made if the gelding presented with typical clinical signs with confirmation at surgery. Thirty‐two cases of SC were identified at the two equine hospitals. The mean age at presentation was 6 years (range 2–14 years, n = 22), and the median time from castration to presentation was 29.5 days (range 20–2500 days). Mean age at castration was 4.3 years (range 6 months to 10 years, n = 10). Clinical signs included scrotal swelling, discharging wounds, hindlimb lameness and pyrexia. Five horses demonstrated hyperfibrinogenaemia (n = 8). Microbial culture isolated various bacterial species. All 32 cases were treated with surgical excision of the infected tissue and discharged from the hospitals between 1 and 10 days post‐operatively. A limitation of this study is that it was a retrospective study with no long‐term follow‐up available. It was concluded that the results of this study confirm that SC can present at variable time points following castration, even many years later, and that a variety of bacterial species may be involved. Surgical excision of infected tissue is a successful treatment with a good short‐term prognosis for survival.